HUBUNGAN ANTARA TUMOR ASSOCIATED- MACROPHAGES (TAMs) , MICROVESSEL DENSITY (MVD) , KADAR PROSTATIC SPECIFIC ANTIGEN (PSA) DENGAN DERAJAT HISTOLOGIS LESI PROSTAT PIN HIGH GRADE DAN ADENOKARSINOMA PROSTAT - , SRI HIDAYAH NURLELA SYAFIIE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Prostatic adenocarcinoma may develops from High grade PIN. The Prostat Specific Antigen (PSA) is a glycoprotein produced primarily by the epithelial cells that line the acini and ducts of the prostate gland. PSA levels increase with the increase of histological grade of prostatic cancer. They might promote prostate cancer and stromal proliferation which the serum levels are elevated. Measurements of the PSA levels correlate significantly and positively with Gleason scores. The other role of the PSA in prostate cancer was inhibit angiogenesis , then PSA levels was not only an Androgen Receptor (AR) target gene, but also participated in the etiology of prostate cancer. Tumor growth and progression involves many factors, including interaction between tumor cells and TAMs. TAMs are main important inflammatory cells of stromal tumor and have important roles in tumor angiogenesis which MVD reflects this process. Studies of TAMs in various human cancers showed significant correlation with tumor angiogenesis, but lack information in prostate cancer. More detailed mechanism regarding the significance between TAMs, MVD and PSA levels in prostate cancers need to be explored and so treatment and prognosis can be determined more accurately. Objective: To investigate significance of TAMs, MVD and PSA levelsin High grade PIN and histological grading of prostatic adenocarcinoma, correlated with histologic grading. Material and Methods: Design of this research was a quantitative non-experimental, performed by cross sectional method. Seventy sixparaffin-embedded tissues of High grade PIN and Prostatic adenocarcinoma, taken from Dr. Sardjito General Hospital in 2009-2011 collected specimens were used in this study. Samples consist of 31 PIN High grade, 19 low grade adenocarcinoma (gleason score â¤ 7), and 26 high grade adenocarcinoma (gleason score 8-10). Expressionof CD68, vWFwere examined using immunohistochemistry methode. PSA level in was examined by serum pasien with Immunoenzymatic assay. The correlation ofeach variable was analyzed with Pearson correlation test. The differentiation of TAMs, vWF and PSA levels in each group was analyzed with ANOVA test. Result: There were significantly correlation between PSA levels with histological grading of prostatic adenocarcinoma and PIN High grade (p= 0,000), but not correlated with TAMs (p = 0,730) and MVD (p = 0,224). TAMs were not statistically significant with histological grading of prostatic adenocarcinoma and PIN High grade (p= 0,608) and MVD (p = 0,600) . MVD was not significant with histological grade of adenocarcinoma and PIN High grade (p= 0,906) Conclusion :This study suggested that PSA levels have important role in the progression of prostatic adenocarcinoma cancer. Meanwhile TAMs and MVD were not influences tumor angiogenesis and progression of prostatic carcinoma